Pengembangan Bahan Ajar Matematika Berbasis Buku Fabel Berkarakter untuk Siswa SMP - Dwi Oktaviana; Iwit Prihatin (Universitas Indraprasta PGRI Jakarta, 2019)
This research is a development research that aims to develop and assess the quality of mathematical teaching materials based on fable books character in a rectangular material that is valid, meets classical completeness, and good student response The type of research used is Research & Development (R & D) research with reference to the Borg & Gall model. The experimental subjects in this study were seventh grade students of MTs Al-huda, Mubung Village, Hulu Gurung Subdistrict, Kapuas Hulu District with a total of 17 students. Based on the results of a limited trial conducted, it was found that (1) the results of character fable book validation obtained the average score of 85,42% with a very valid category so there was no need to revise and experts stated that the developed fable character was feasible to be used and can be tested in the field, (2) the results of testing the use of products through student learning outcomes tests obtained classical completeness were 76,47% so as to achieve classical completeness where the completeness of classical completeness set at MTs Al-huda Mubung Village is 70%, and (3) student responses to Mathematical teaching materials based on fable books with character with an average score of 87,54% with a very good category